NEUTRACEUTICAL POTENTIAL OF ORGANOSULFUR COMPOUNDS IN FRESH GARLIC AND GARLIC PREPARATIONS - KATARE CHARU,; SHRIVASTAVA YOGITA,; SAXENA SONALI, (International Journal of Pharma and Bio Sciences, 2014)
Garlic (Allium sativum L.), one of the best-researched herbal remedies, holds a distinctive position in history, traditionally used to treat infection, colds, heart disease, diabetes, and other disorders. Clinically, it has been experimented or reducing blood pressure, cholesterol, and glucose level, as well as defense against arteriosclerosis and cancer. Other therapeutic properties of garlic and garlic preparations include antibacterial, antithrombotic, antioxidant, immunomodulatory, antidiabetic actions and modulation of drug metabolism. Presence of certain constituents such as organo-selenium compounds steroid saponins and sapogenins (e.g. β-chlorogenin) have been demonstrated in recent studies. Garlic is also reported to contain vitamin B6 and B12 flavonoids, lectins and N-fructosyl-aminoacids, which may contribute, along with organo-sulphur compounds, to the above mentioned biological effects of this herb. This review summarizes the research findings on garlic and its sulfur-containing compounds in preventing cardiovascular diseases, diabetes and cancer, along with antioxidant, antimicrobial and immunimodulatory activities.This review highlights potential biological role of garlic and views its promising role in disease prevention.